Dynamics and variability of the Subantarctic mixed-layer as determined from a high resolution glider dataset - Du Plessis, Marcel David (Department of Oceanography, 2015)
Traditional understanding of mixed-layer (ML) dynamics in the African sector of the Southern Ocean suggests that seasonal summer stratification and subsequent reduction in ML depth (MLD) is determined by the onset of a positive net heat ux. The impact of physical forcing mechanisms on the intra-seasonal variability of the ML is still relatively unknown. Recent research in the North Atlantic has highlighted the role that sub-mesoscale ML eddy dynamics has on ML stratification. It is now understood that large horizontal density gradients drive sub-mesoscale eddy formation which have been shown to result in the early onset of spring phytoplankton blooms at high latitudes. To date these ML eddies have been researched primarily in models with few observational studies available. To test the ML eddy hypothesis in the Subantarctic Zone (SAZ) we use high-resolution (~3km, 4-hourly) glider measurements between austral spring to late summer.